The THE EFFECTS OF COMPOSTS AND NPK DOSAGE TO THE GROWTH OF OIL PALM (Elaeis guineensis Jacq) AT MAIN NURSERY - Siahaan, Megawati; Hamzah Manurung; Emil Adolf Behring Silalahi (Agro Estate, 2024)
One of the problems in nursery is difficulties to find topsoil and  using of subsoil will be alternative. The objectives of this research were knowing the effects of kinds of compost, compound NPK dosage and interaction of them at oil palm in main nursery. Randomized block design was used with kinds of compost (J) and compound NPK dosage (D) as treatments; without compost (J1),  rice straw compost (J2), sawdust compost (J3) and empty palm oil bunches compost (J4); without compund NPK (D0), ½ of recomendation compound NPK dosage (D1), ¾ of  recomendation compound NPK dosage (D2) and ¾ of recommendation compound NPK dosage (D3); The research shows that height of plant at 6-12 weeks after planting, amount of leave at 10-12 weeks after plantings, stem diameter 7-12 weeks after planting,  fresh weight of  shoot and root at 12 weeks after plantings are significantly affected by kinds of compost (J). Heigh of plants at 6-12 weeks after plantings, stem diameter at 6-12 weeks after plantings, fresh and dry shoot weight at 12 weeks after planting are significantly affected by Compound NPK dosage.  Heigh of plants at 7-12 weeks after planting, stem diameter 3-5 weeks after planting, dried roots weight at 12 weeks after planting are affected by interaction of kinds of compost and  compound NPK dosage. J3 as compost from oil palm empty bunch; D3 as recommendation dosage compound NPK and K3D2 is better than the others.